O revestimento refratário e seu efeito na vida útil e no consumo energético de calcinadores de alumina - Teider, Bruno Henrique (Universidade Federal de São Carlos, 2012)
The increased need of reducing production costs of commodities raised the importance of reaching higher levels of process efficiency and also the consolidation of financial gains due to larger-scale production capacities. In this scenario, the control and reduction of energy consumption is considered one of the most critical issues due to its impact on the companies economical, environmental and social businesses sustainability. In the primary alumina industry, it is estimated that the calcination process still demands 30% in excess of energy to operate, although there have been major improvements in the current calciners when compared to the former versions disseminated in the 70 s. In parallel, although the production capacity increased significantly, diluting the overall production costs, they also raised the importance of maintaining their operational availabilities at the maximum level to attain the financial viability of the processes. Currently, daily losses are estimated to be close to 1 million dollars per each nonproductive day of a large-capacity calciner. Despite this critical aspect, it is not rare to find literature reports indicating refractory failure as one of the main causes of unexpected production halts, which highlights the need of high performance linings as a pre-requisite for longer campaigns and lower levels of energy consumption. This project evaluated one of these refractory failure detected in three new large-capacity calciners. The root-cause of the refractory s short life was identified and afterwards a novel more suitable material was selected increasing twofold the operational campaign time, which resulted in additional potential revenue of 60 million dollars per year. In order to complement the study, the overall reduction of energy consumption was quantified for different high performance insulating materials. This project was concluded with an economical viability study for the implementation of this novel insulating lining concept for those three calciners.
The Refractory Lining and its Effect on the Life Time and Energy Consumption of Alumina Calciners
Keywords: Materiais refratários; Calcinadores de leito fluidizado; Alumina; Energia; Análise de falha; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA